In vivo, high‐frequency three‐dimensional cardiac MR elastography: Feasibility in normal volunteers. Issue 1 (17th January 2016) - Arani, Arvin; Glaser, Kevin L.; Arunachalam, Shivaram P.; Rossman, Phillip J.; Lake, David S.; Trzasko, Joshua D.; Manduca, Armando; McGee, Kiaran P.; Ehman, Richard L.; Araoz, Philip A.
Abstract : Purpose: Noninvasive stiffness imaging techniques (elastography) can image myocardial tissue biomechanics in vivo. For cardiac MR elastography (MRE) techniques, the optimal vibration frequency for in vivo experiments is unknown. Furthermore, the accuracy of cardiac MRE has never been evaluated in a geometrically accurate phantom. Therefore, the purpose of this study was to determine the necessary driving frequency to obtain accurate three‐dimensional (3D) cardiac MRE stiffness estimates in a geometrically accurate diastolic cardiac phantom and to determine the optimal vibration frequency that can be introduced in healthy volunteers. Methods: The 3D cardiac MRE was performed on eight healthy volunteers using 80 Hz, 100 Hz, 140 Hz, 180 Hz, and 220 Hz vibration frequencies. These frequencies were tested in a geometrically accurate diastolic heart phantom and compared with dynamic mechanical analysis (DMA). Results: The 3D Cardiac MRE was shown to be feasible in volunteers at frequencies as high as 180 Hz. MRE and DMA agreed within 5% at frequencies greater than 180 Hz in the cardiac phantom. However, octahedral shear strain signal to noise ratios and myocardial coverage was shown to be highest at a frequency of 140 Hz across all subjects. Conclusion: This study motivates future evaluation of high‐frequency 3D MRE in patient populations. Magn Reson Med 77:351–360, 2017. © 2016 Wiley Periodicals, Inc.